STUDI ETNOBOTANI TUMBUHAN OBAT DI DUSUN KELAMPUK KECAMATAN TANAH PINOH BARAT KABUPATEN MELAWI - haida, Nur; Usman, Fadillah H.; Tavita, Gusti Eva (Universitas Tanjungpura, 2015)
Kelampuk village at Land Pinoh West Sub District Melawi District people have traditionally used medicinal plants that are nearby to treat various diseases. The aim of this study was to determine the types of medicinal plants and their use by communities around the Kelampuk village Land Pinoh West sub district Melawi District This study using snowball sampling techniques or performed in sequence to ask for information on people who have been interviewed or contacted in advance. Results of research concluded that the most widely type of plant commonly used are 51 species from 41 family. The level of habitus are 24 herbaceous species. While based part in use, then mostly the leaves as many as 31 species. Then, by way of processing by way of ground as many as 23 species, and if viewed the use of that method taped as many as 24 species. While based on the use to treat diseases of the outside there are 32 species, and based on the form of a single herb potion then there are 51 species. From the data, it turns a kind of medicinal herbs can treat more than one disease. Keywords: Ethnobotany, Kelampuk village, Medicinal plants Melawi Distrct.